PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL - Widianti, Eka Amelia; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
ABSTRACTThe purpose of this research is to find out the influence of profitability, firm size, and assets structure to the structure of banking companies which are listed in Indonesia Stock Exchange during the period of 2010-2013. The samples are 17 banking companies which are listed in Indonesia Stock Exchange (IDX) and these banking companies have been selected by using purposive sampling technique. The analysis technique has been done by performing multiple regressions and classic assumption which consist of normality test, multicolinearity test, heteroscedasticity test, and autocorelation test. Meanwhile the hypothesis test has been done by using goodness of fit and t test which is done by using SPSS program version 16. Based on the result of multiple regressions analysis with the significance level of 5%, therefore it shows that: (1). H1 is profitability which has influence to the capital structure and which shows a negative direction, (2). H2 is firm size which has influence to the capital structure and which shows positive direction, and (3) H3 is assets structure which has influence to the capital structure and which show positive direction. Therefore, the firm size and assets structure have positive influence to the capital structure.Keywords: Profitability, Firm Size, Assets Structure and Capital Structure.